Screening for Erdoğanism: Television, post-truth and political fear. (August 2020) - Çelik , Burçe
The majority of current political communication studies focuses on digital and social media, and overlooks the centrality of television for the production and endurance of strongman politics in the Global South. By focusing on the journalistic television productions aired during the June 2018 election period in Turkey, this article unpacks the televisual logic that is incarnated in different modalities of telling and narrating of televisual genres. I propose two main themes: the 'political fear' of physical and social security threats, and 'post-truth communications' as the main televisual idioms for a vision of the future that is either secure or chaotic, that is, with or without Erdoğan. By combining political economy, content and textual analysis, I scrutinise the production dynamics of the televisual economy and the control and content of factual segments.